The Dynamics of ‘The British Identity’ as a Concept in Contemporary British Mass Media: A Discursive Analysis - V. I. Suslov (Дискурс профессиональной коммуникации, 2023)
This article explores the multifaceted nature of “The British Identity” within the context of political discourse, focusing on its representation in The Guardian newspaper. The aim of this study is to investigate the content specificity of the concept and its transformation under the influence of socio-cultural and extralinguistic factors. Through a qualitative analysis of selected articles from The Guardian, the paper examines the linguistic units used to represent the British identity and the evaluative nature of their expression. The study adopts a conceptual framework that considers the British identity as a political and cultural concept, susceptible to diverse interpretations and judgments within the ideological context. By employing a content analysis approach, the research reveals the tensions arising from the attempt to cater to both conservative and progressive factions of the UK society. The findings indicate that the representation of the British identity in The Guardian is influenced by socio-cultural factors, reflecting the evolving dynamics of British society. The analysis highlights the presence of evaluative expressions, reflecting the conceptual domain’s evaluative nature and its connection to political and cultural debates, particularly those concerning multiculturalism. While the study predominantly relies on articles from The Guardian, it acknowledges the need for broader source diversity to capture a more comprehensive understanding of the British identity. Moreover, the paper suggests that further research in this field holds promise for exploring the evolution and adaptation of conceptual domains in an ever-changing world. This study contributes to the existing body of knowledge by shedding light on the complex and evolving nature of the British identity within political discourse. The research serves as a foundation for future investigations into the concept of identity and its representation in professional media outlets, and its implications for social cohesion in diverse societies.